Q: -3n plus 5n plus 4 equals -4 solve for n?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3n + 2n = 25 5n = 25 n = 5

22n + 2.

4 = -5n + 6n2 if you want to solve for n: 6n2 - 5n - 4 = 0 (3n - 4)(2n + 1) = 0 3n - 4 = 0, n = 4/3 2n + 1 = 0, n = -1/2 n = {-1/2, 4/3}

A - B = -3n + 2 - (5n - 7) = -3n + 2 - 5n + 7 = 9 - 8n

5n-2+2=4n 5n=4n n=0

Related questions

4n

3n+5n=8n

3n + 2n = 7 + 4n 5n = 7 + 4n 5n - 4n = 7 n = 7

3n + 2n = 25 5n = 25 n = 5

5n = 2n + 3n .

22n + 2.

7n - 2 + 3n + 4 = 7n + 3n - 2 + 4 = 10n + 2 which can be simplified to 2(5n +1)

5n + 12 = 3n Try to get all expressions with n on the left side 5n + 12 - 3n = 3n - 3n 2n + 12 = 0 Try to get rid of 12 on the left side 2n + 12 - 12 = -12 2n = -12 n = -12/2 = -6

4 = -5n + 6n2 if you want to solve for n: 6n2 - 5n - 4 = 0 (3n - 4)(2n + 1) = 0 3n - 4 = 0, n = 4/3 2n + 1 = 0, n = -1/2 n = {-1/2, 4/3}

Subract 5n from both sides and you get 9=-3n, then divide bother sides by -3 and you get n= -3

A - B = -3n + 2 - (5n - 7) = -3n + 2 - 5n + 7 = 9 - 8n

5n-2+2=4n 5n=4n n=0